Alfaxalone improved in acute stress‐induced tactile hypersensitivity and anxiety‐like behavior in mice - Kazumi Yoshizawa; Saki Ukai; Junpei Kuroda; Tsugumi Yamauchi; Daisuke Yamada; Akiyoshi Saitoh; Satoshi Iriyama; Shoichi Nishino; Satoru Miyazaki (Wiley, 2022)
Abstract Stress has been shown to affect brain activity and exert potent and complex modulatory effects on pain. Several behavioral tests have shown that acute stress produces hyperalgesia, depending on the stress conditions. In the present study, we investigated the effects of single restraint stress on the tactile threshold and anxiety sensitivity in mice. Mice were evaluated for the tactile threshold using von Frey filaments and for anxiety sensitivity using the elevated plus maze (EPM) test. Tactile thresholds were lowered by both 2 and 4 hour of restraint stress, but anxiety‐like behaviors were observed only after 4 hour of restraint stress in the EPM test. In addition, we found that alfaxalone, which is a positive allosteric modulator of the γ‐aminobutyric acid (GABA)A receptor, prevented restraint stress‐induced hyperalgesia‐like and anxiety‐like behaviors. These results indicate that GABAergic function appears to be critical in the regulation of physical stress‐induced hyperalgesia and anxiety.